健康是本钱 - Health is my capital: a qualitative study of access to healthcare by Chinese migrants in Singapore - Wai Jia Tam; Wei Leong Goh; Jeffrey Chua; Helena Legido-Quigley (BMC, 2017)
Abstract Background Since the 1970s, Singapore has turned into one of the major receiving countries of foreign workers in Southeast Asia. Over the years, challenges surrounding access to healthcare by Chinese migrant workers have surfaced globally. This study aims to explore the experiences of Chinese migrants accessing primary and secondary/tertiary healthcare in Singapore, and the opportunities for overcoming these barriers. Methods We conducted 25 in-depth interviews of 20 Chinese migrants and five staff from HealthServe, a non-governmental organization serving Chinese migrants in Singapore from October 2015 to January 2016. Interviews were transcribed and analysed inductively adopting thematic analysis. Results Chinese migrants in Singapore who were interviewed are mainly middle-aged breadwinners with multiple dependents. Their concept of health is encapsulated in a Chinese proverb "健康是本钱", meaning "health is my capital". Health is defined by them as a personal asset, needed to provide for their families. From their health-seeking behaviors, six pathways were identified, highlighting different routes chosen and resulting outcomes depending on whether their illness was perceived as major or minor, and if they sought help from the private or public sector private or public sector. Key barriers were identified relating to vulnerabilities during the migration process, during their illness, when consulting with healthcare providers, and during repatriation. A transactional doctor-patient culture in China contrasts with the trust migrants place in Singaporean's public health system, perceived as equitable and personable. However, challenges remain for injured migrants who sought help from the private sector and those with chronic diseases. Conclusions Policy recommendations to increase patient autonomy enabling choice of healthcare provider and provide for non-work related illnesses are suggested. Partnerships between migrant advocacy organizations and various stakeholders such as hospitals, government agencies and employers can be strengthened.